Behavior of the breathing pyrochlore lattice Ba3Yb2Zn5O11 in applied magnetic field*This manuscript has been authored by UT-Battelle, LLC under Contract No. DE-AC05-00OR22725 with the U.S. Department of Energy. The United States Government retains and the publisher, by accepting the article for publication, acknowledges that the United States Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. The Department of Energy will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (19th October 2018) - Rau, J G; Wu, L S; May, A F; Taylor, A E; Liu, I-Lin; Higgins, J; Butch, N P; Ross, K A; Nair, H S; Lumsden, M D; Gingras, M J P; Christianson, A D
Abstract: The breathing pyrochlore lattice material Ba3 Yb2 Zn5 O11 exists in the nearly decoupled limit, in contrast to most other well-studied breathing pyrochlore compounds. As a result, it constitutes a useful platform to benchmark theoretical calculations of exchange interactions in insulating Yb 3+ magnets. Here we study Ba3 Yb2 Zn5 O11 at low temperatures in applied magnetic fields as a further probe of the physics of this model system. Experimentally, we consider the behavior of polycrystalline samples of Ba3 Yb2 Zn5 O11 with a combination of inelastic neutron scattering and heat capacity measurements down to 75 mK and up to fields of 10 T. Consistent with previous work, inelastic neutron scattering finds a level crossing near 3 T, but no significant dispersion of the spin excitations is detected up to the highest applied fields. Refinement of the theoretical model previously determined at zero field can reproduce much of the inelastic neutron scattering spectra and specific heat data. A notable exception is a low temperature peak in the specific heat at ̃0.1 K. This may indicate the scale of interactions between tetrahedra or may reflect undetected disorder in Ba3 Yb2 Zn5 O11 .